Factors that influence engagement in pre-proceedings practice: presenting the roles of professionals working within the family justice system through personal narratives. Issue 1 (2nd January 2016) - Holt, Kim; Kelly, Nancy
Abstract : Public discourse around changes introduced as part of a drive to tackle spending on welfare, reflect a less than tolerant attitude towards welfare generally, but more specifically towards parents who require state involvement to care safely for their children. The introduction of a deadline of 26 weeks for the completion of care proceedings, together with a clear steer to resolve disputes wherever possible prior to making an application to court has introduced further instrumental approaches to working with parents. In this paper we explore practitioner experiences and understandings of working within the new legislative frameworks and consider the dominant cultural narratives they are working within. However, in some cases professionals felt able to challenge the economic narrative of the pre-proceedings protocol, and they experienced the legal and policy changes as an opportunity to engage in a helping alliance with families with the provision of support that otherwise they would not have been able to offer.